Testing agro-ecological adaptation of improved herbaceous forage legumes in South-Kivu, D.R. Congo - Katunga Musale, Dieudonné; Muhigwa, JBB; Kashala, KJC; Ipungu, L; Nyongombe, N; Maass, Brigitte L.; Peters, Michael (Scientific Research Publishing, Inc., 2014)
In tropical african countries where livestock is either reared in herds on natural grasslands or individuallly tethered to herds on natural or spontaneous vegetation, the productivity is low, especially during the dry season. Using improved forages could play an important role in both enhancing livestock production and improving soil fertility and preventing from soil erosion. Eleven herbaceous forage legumes previously tested in tropical South America and South Asia by CIAT were tested in South-Kivu, D. R. Congo. Across sites, Stylosanthes guianensis, Desmodium uncinatum, Centrosema molle and Canavalia brasiliensis had a highest yield, nowhere Vigna unguiculata adapted. Differencial plant adaptation occured, e.g. Clitoria ternatea being well adaptated only in the midlands with good soils, where the mean of dry mater leaf yield was higher. Farmer evaluation emphazied overall biomass production with preference in the highlands, farmers chose Desmodium uncinatum, Canavalia brasiliensis and Lablab purpureus 21603 and in the midlands Stylosanthes guianensis 11995 and Lablab purpureus 22759. Farmer evaluation confirmed the best yield fit herbaceous forage legumes.